Flaky phosphorus / titanium carbide compound as well as preparation method and application thereof

The preparation of sheet-shaped phosphorus/titanium carbide composites by solid-phase high-temperature and high-pressure method was solved, and the problem of large structural changes and low efficiency of the red phosphorus negative electrode material during the charging and discharging process was achieved, and the coexistence of high specific capacity, long cycle life and excellent rate performance was achieved.

CN119725460APending Publication Date: 2025-03-28ZHONGYUAN ENGINEERING COLLEGE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411915786.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In existing sodium ion batteries, the crystal structure of the red phosphorus negative electrode material changes greatly during the charging and discharging process, resulting in low charge and discharge efficiency of the first circle, poor cycle life, and poor rate performance.

Method used

The sheet-shaped phosphorus/titanium carbide composite was prepared by a one-step solid-phase high-temperature and high-pressure method. The red phosphorus undergoes incomplete crystalline transformation, forming a red phosphorus-black phosphorus heterophase junction. The titanium carbide nanosheets serve as the loading site and shape template to form a nanosheet-shaped composite.

Benefits of technology

The specific capacity and circulation capacity retention rate of the phosphorus negative electrode are significantly improved. The specific capacity of the first round can reach 1143.4 mA h/g, and the capacity retention rate after 100 cycles can reach 60.9%, and the rate performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725460A_ABST
    Figure CN119725460A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of rechargeable batteries, and relates to an electrode material for a sodium ion battery. The invention provides a preparation method of a flaky phosphorus / titanium carbide compound, which comprises the following steps: firstly, uniformly mixing red phosphorus powder and titanium carbide nanosheets, pressing into a compact block body by a tabletting method, then putting the block body into a press machine, and performing high-temperature and high-pressure treatment for a certain time to induce red phosphorus to be converted into a red phosphorus-black phosphorus out-phase junction, thereby obtaining the flaky phosphorus / titanium carbide compound. And uniformly loading on the surface of the titanium carbide nanosheet to finally obtain the flaky phosphorus / titanium carbide compound. According to the preparation method of the flaky phosphorus / titanium carbide compound disclosed by the invention, the nano flaky phosphorus / titanium carbide compound can be rapidly prepared, the volume effect and the structure collapse of a phosphorus negative electrode are effectively relieved, and the specific capacity and the capacity retention rate of the phosphorus negative electrode are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of rechargeable batteries and relates to electrode materials for sodium ion batteries. Background Art

[0002] Among the negative electrode materials for sodium-ion batteries, red phosphorus has the advantages of high specific capacity and wide sources of raw materials. Red phosphorus is a common sodium storage negative electrode material with a high theoretical specific capacity (2596 mA h / g), so it is a sodium-ion battery electrode material with broad application potential. Although red phosphorus has many advantages, since the sodium storage process of this material is mainly based on alloying reaction, the crystal structure changes greatly during the charging and discharging process and the particles are severely pulverized, resulting in low first-cycle charging and discharging efficiency and poor cycle life; at the same time, due to the relatively low electronic / ionic conductivity of red phosphorus, when the battery is charged and discharged with large currents, the rate performance of the material is poor.

[0003] In recent years, researchers have tried a variety of modification methods (nano-sizing, porosification, carbon coating / composite, conductive polymer coating, etc.) to try to improve the electrochemical performance of phosphorus negative electrodes. The application with publication number CN111785946A discloses a negative electrode active material in which the red phosphorus monomer is deposited into a porous TiO2 nanosheet matrix by evaporation. The material requires two steps of high-temperature treatment. However, these conventional modification methods still cannot obtain satisfactory comprehensive electrochemical performance, especially coexisting sodium ion negative electrode materials with high specific capacity, long cycle life and excellent rate performance. In addition, some methods still have problems such as complex process, uneven product composition, expensive raw materials or serious pollution, which are not conducive to the large-scale industrial application of materials. Therefore, it is necessary to develop a simpler and more effective new modification strategy to improve the comprehensive sodium storage performance of phosphorus negative electrodes. In recent years, some researchers have proposed to use red phosphorus as raw material to prepare red phosphorus / black phosphorus / graphene composite negative electrode, which shows better sodium storage performance than red phosphorus / graphene and black phosphorus / graphene. However, this study used ethylenediamine, which is easy to make explosive, as solvent and three-dimensional nitrogen-doped graphene, which is more expensive, as carrier. The red phosphorus / black phosphorus composite was prepared by a time-consuming solvent thermal method, which is difficult to promote and use on a large scale. However, if red phosphorus is used as raw material and the conventional solid-phase high temperature and high pressure method is used to produce red phosphorus / black phosphorus composite, there are problems such as difficult to control the components of the final product and easy formation of large-sized particles. It is impossible to prepare a red phosphorus / black phosphorus composite with a special nanostructure, and its comprehensive electrochemical sodium storage performance is limited compared to the pure red phosphorus negative electrode. Therefore, how to achieve the simple and low-cost preparation of high-performance sodium-ion batteries with red phosphorus / black phosphorus composites with special nanostructures is a key technical problem that needs to be solved in this industry. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a flaky phosphorus / titanium carbide composite and a preparation method and application thereof.

[0005] The technical solution of the present invention is achieved in this way: A method for preparing a flaky phosphorus / titanium carbide composite comprises the following steps: pressing a mixture of red phosphorus and titanium carbide nanosheets into a dense block, then applying high temperature and high pressure to the block for a certain period of time to induce an incomplete crystal transformation of the red phosphorus, thereby preparing the flaky phosphorus / titanium carbide composite.

[0006] Taking the total mass of the mixture as 100%, the amount of red phosphorus as X, and the amount of titanium carbide as 100%-X, the mass proportion of titanium carbide is 5%-50%, and the preferred proportion is 5%-20%; The mass ratio of the red phosphorus to the titanium carbide nanosheets is 10-19:1-10, preferably 1-19:1.

[0007] The above-mentioned high temperature is 200-800°C and the high pressure is 1-8 Gpa.

[0008] Preferably, the high temperature is 300-700° C. and the high pressure is 2-6 GPa.

[0009] Specifically, the preparation method of the flaky phosphorus / titanium carbide composite provided in the present application comprises the following steps: (1) Weigh a certain proportion of red phosphorus and titanium carbide nanosheets and mix them evenly, then load them into a powder tablet press mold and compact them into blocks; (2) placing the block in a sealed mold and placing it in a six-sided top press, applying a certain pressure and temperature to the mold, and then cooling it to room temperature to obtain a flake phosphorus / titanium carbide composite; the press is a six-sided top press; the pressure applied by the press is 1-8 GPa, preferably 2-6 GPa; the temperature applied by the press is 200-800°C, preferably 300-700°C; The present application also provides a flaky phosphorus / titanium carbide composite prepared by the above method.

[0010] The flaky phosphorus / titanium carbide composite comprises elemental phosphorus and titanium carbide nanosheets, wherein the red phosphorus-black phosphorus heterogeneous junction is coated on the surface of the titanium carbide nanosheets to form a phosphorus / titanium carbide composite.

[0011] Again, the present application also provides a negative electrode material which is a flaky phosphorus / titanium carbide composite.

[0012] A sodium ion battery prepared using the above-mentioned negative electrode material.

[0013] The present invention has the following beneficial effects: 1. The present invention is the first to prepare a flaky phosphorus / titanium carbide composite by a one-step solid phase high temperature and high pressure method. High temperature and high pressure induce an incomplete crystal transformation of red phosphorus to form a red phosphorus-black phosphorus heterophase junction, and the flaky titanium carbide provides a loading site and shape template for red phosphorus / black phosphorus, forming a nano-flaky phosphorus / titanium carbide composite.

[0014] 2. The flaky phosphorus / titanium carbide composite prepared by the present invention has elemental phosphorus particles uniformly loaded on the surface of titanium carbide nanosheets, which can provide more sodium storage sites when used as a sodium storage negative electrode, thereby improving the specific capacity of the phosphorus negative electrode. In addition, the nanosheet structure of the composite effectively alleviates the volume effect and structural collapse of the phosphorus negative electrode, and improves the cycle capacity retention rate of the phosphorus negative electrode. The first cycle specific capacity of the sodium ion battery prepared by the present application can reach 1143.4 mA h / g, and the capacity retention rate can reach 60.9% after 100 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 This is a scanning electron microscope photograph of the sample prepared in Comparative Example 2 of the present invention.

[0017] Figure 2 This is a scanning electron microscope photograph of the sample prepared in Example 2 of the present invention.

[0018] Figure 3 This is the X-ray diffraction pattern of the sample prepared in Example 7 of the present invention.

[0019] Figure 4 This is a high-resolution TEM image of a local area of ​​the surface of the sample prepared in Example 7 of the present invention.

[0020] Figure 5 This is the cycle performance of the samples prepared in Comparative Example 1 and Example 10 of the present invention when used as sodium storage negative electrodes. DETAILED DESCRIPTION

[0021] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Unless otherwise specified, the experimental methods used in the following experimental examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0023] Example 1 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 95:5, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0024] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 5 GPa, the temperature was quickly raised to 600°C and the temperature and pressure were maintained for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0025] Example 2 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 90:10, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0026] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 5 GPa, the temperature was quickly raised to 600°C and the temperature and pressure were maintained for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0027] Example 3 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 80:20, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0028] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 5 GPa, the temperature was quickly raised to 600°C and the temperature and pressure were maintained for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0029] Example 4 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 50:50, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0030] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 5 GPa, the temperature was quickly raised to 600°C and the temperature and pressure were maintained for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0031] Example 5 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 85:15, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0032] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 5 GPa, the temperature was quickly raised to 300°C and the temperature and pressure were maintained for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0033] Example 6 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 85:15, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0034] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 5 GPa, the temperature was quickly raised to 500°C and the temperature and pressure were maintained for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0035] Example 7 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 85:15, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0036] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 5 GPa, the temperature was quickly raised to 700°C and the temperature was maintained at this temperature for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0037] Example 8 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 85:15, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0038] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 5 GPa, the temperature was quickly raised to 900°C and the temperature and pressure were maintained for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0039] Example 9 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 85:15, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0040] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 2 GPa, the temperature was quickly raised to 600°C and the temperature and pressure were maintained for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0041] Example 10 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 85:15, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0042] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 4 GPa, the temperature was quickly raised to 600°C and the temperature and pressure were maintained for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0043] Embodiment 11 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 85:15, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0044] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 6 GPa, the temperature was quickly raised to 600°C and the temperature and pressure were maintained for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0045] Example 12 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 85:15, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0046] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 9 GPa, the temperature was quickly raised to 600°C and the temperature and pressure were maintained for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0047] Example 13 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 85:15, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0048] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 9 GPa, the temperature was quickly raised to 600°C and the temperature and pressure were maintained for 1 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0049] Embodiment 14 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 85:15, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0050] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 9 GPa, the temperature was quickly raised to 600°C and the temperature and pressure were maintained for 60 min. It was then quickly cooled to room temperature to obtain the final reaction product.

[0051] Comparative Example 1 The preparation method of the flaky phosphorus negative electrode material of this embodiment comprises the following steps: (1) The red phosphorus is mixed and ground evenly, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0052] Comparative Example 2 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Grind the red phosphorus evenly and then load it into a small tablet press to form a pre-densified block.

[0053] (2) The block was placed in a sealed mold and then put into a six-sided press. After the pressure was applied to 5 GPa, the temperature was quickly raised to 600°C and the temperature and pressure were maintained for 5 min. The block was then quickly cooled to room temperature to obtain the final reaction product.

[0054] Comparative Example 3 The preparation method of the flaky phosphorus / titanium carbide composite of this embodiment comprises the following steps: (1) Red phosphorus and titanium carbide nanosheets were mixed and ground evenly in a mass ratio of 80:20, and then loaded into a small tablet press to be pressed into a preliminarily densified block.

[0055] Application Examples The samples prepared in the above examples and comparative examples were mixed with Ketjen black and polyvinylidene fluoride in a mass ratio of 7:2:1 and ground, and then a proper amount of nitrogen-methyl pyrrolidone was added to prepare a slurry, which was then coated on a copper foil and dried to obtain an electrode sheet.

[0056] The above-mentioned disc electrode was used as the working electrode, the homemade sodium sheet was used as the counter electrode, the glass fiber filter membrane was used as the diaphragm, and 1 mol / L NaClO4 / propylene carbonate + ethylene carbonate solution (10%wt fluoroethylene carbonate additive) was used as the electrolyte to assemble a button battery in an argon-protected glove box.

[0057] (3) Battery performance test During the battery cycle life test, the current density was set to 200 mA / g, the voltage range was set to 0-2 V, and the ratio of the 100th cycle / 1st cycle charging capacity was taken as the 100-cycle capacity retention rate.

[0058] The results are shown in Table 1: Table 1 Performance comparison table of various embodiments It can be seen from the comparison table of each embodiment that the sample in comparative example 1 did not contain titanium carbide and was not subjected to solid phase high temperature and high pressure treatment; the sample in comparative example 2 was subjected to high temperature and high pressure treatment, but did not contain titanium carbide; the sample in comparative example 3 contained titanium carbide but was not subjected to high temperature and high pressure treatment.

[0059] Titanium carbide was added to the samples of Examples 1-12, and they were also treated with high temperature and high pressure. From the performance test results, it can be seen that the first cycle specific capacity of the samples of Examples 1-12 is higher than that of Comparative Examples 1-3, and the capacity retention rate is higher than that of Comparative Examples 1-3, indicating that compared with unmodified red phosphorus, red phosphorus without adding flaky titanium carbide, and red phosphorus without high temperature and high pressure treatment, the flaky phosphorus / titanium carbide composite prepared in this application can significantly improve the specific capacity and capacity retention rate of the phosphorus negative electrode.

[0060] It can be seen from Comparative Example 2 and Examples 1-4 that the present application can improve the first-cycle specific capacity and capacity retention rate of the sample by adjusting the proportion of titanium carbide. Figure 1 This is a SEM photograph of the sample prepared in Comparative Example 2 of the present invention. When titanium carbide is not added to the raw material, it can be seen that the prepared product is a micron-sized block without any special nanostructure. Figure 2 This is a SEM photo of the sample prepared in Example 2 of the present invention. After titanium carbide is added to the raw material, it can be seen that the prepared product is a nano-sheet. The interior of these sheets is a titanium carbide nanosheet with sharp edges, and the surface of the nanosheet is coated with phosphorus to form a composite. During the solid-phase high-temperature and high-pressure treatment, a large amount of red phosphorus is loaded on the surface of the titanium carbide nanosheet and undergoes a crystal transformation, and finally a phosphorus / titanium carbide composite with a flaky nanostructure is obtained. When the titanium carbide content in the composite is low, increasing the titanium carbide content can provide more loading sites for elemental phosphorus and improve the conductivity of the phosphorus negative electrode. However, the sodium storage specific capacity of titanium carbide is very low, so excessive addition of titanium carbide will result in a decrease in the first-cycle specific capacity of the composite.

[0061] It can be seen from Comparative Example 3 and Examples 5-8 that the present application can improve the first-cycle specific capacity and capacity retention rate of the sample by adjusting the temperature applied to the sample. Figure 3 This is the XRD of the sample prepared in Example 7 of the present invention. It can be seen that red phosphorus phase, black phosphorus phase and titanium carbide phase exist in the sample at the same time. Figure 4 This is a high-resolution TEM image of a local area of ​​the sample surface prepared in Example 7 of the present invention. It can be seen that the crystalline black phosphorus phase is wrapped in the amorphous red phosphorus phase texture to form a heterogeneous junction. However, when the applied temperature is too high, the first cycle specific capacity of the sample decreases and the capacity retention rate also decreases. This is because too high a temperature will cause local particle agglomeration and growth of elemental phosphorus on the surface of titanium carbide nanosheets, destroying the uniformity of the sheet-like phosphorus / titanium carbide composite.

[0062] It can be seen from Comparative Example 3 and Examples 9-12 that the present application can improve the first-cycle specific capacity and capacity retention rate of the sample by adjusting the pressure applied to the sample. Figure 5 It is the cycle performance of the samples prepared in Comparative Example 1 and Example 10 of the present invention. As can be seen from the figure, the first-cycle specific capacity of the sample in Comparative Example 1 is 830.5 mA h / g, and the capacity retention rate is 11.9% after 100 cycles, showing a lower first-cycle specific capacity and capacity retention rate. In contrast, the first-cycle specific capacity of the sample in Example 10 can reach 1143.4 mA h / g, and the capacity retention rate can reach 60.9% after 100 cycles. Analysis shows that after a certain high temperature and high pressure treatment is applied to the sample, the red phosphorus particles in the sample will be evenly dispersed on the surface of the titanium carbide nanosheets, reducing the volume effect of the phosphorus negative electrode during the charge and discharge process and improving the conductivity of the phosphorus negative electrode. In addition, a crystal transformation will occur on the surface of the red phosphorus particles under high temperature and high pressure, and the generated black phosphorus can improve the structural stability of the phosphorus negative electrode. However, when the applied pressure is too high, the first-cycle specific capacity and capacity retention rate of the sample decrease. This is because excessive pressure will cause the elemental phosphorus on the surface of the titanium carbide nanosheets to agglomerate and grow, destroying the uniformity of the nanosheet phosphorus / titanium carbide composite and reducing the first-cycle specific capacity and capacity retention rate of the sample.

[0063] It can be seen from Examples 12-14 that the present application can change the first-cycle specific capacity and capacity retention rate of the sample by adjusting the time of applying high temperature and high pressure treatment to the sample. The treatment time of Example 13 is very short, and the proportion of red phosphorus undergoing phase transformation is low, so the first-cycle specific capacity and capacity retention rate of the sample are lower than those of Example 12; the treatment time of Example 14 is too long, resulting in the phase transformation of red phosphorus to form black phosphorus and further growth, and its first-cycle specific capacity and capacity retention rate are also lower than those of Example 12.

[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a flaky phosphorus / titanium carbide composite, characterized in that: The method comprises the following steps: uniformly mixing red phosphorus and titanium carbide nanosheets, and then pressing them into blocks; and inducing incomplete crystal transformation of red phosphorus through high temperature and high pressure treatment to obtain a flaky phosphorus / titanium carbide composite.

2. The method for preparing the flaky phosphorus / titanium carbide composite according to claim 1, characterized in that: The mass ratio of the red phosphorus to the titanium carbide nanosheets is 10-19:1-10.

3. The method for preparing the flaky phosphorus / titanium carbide composite according to claim 2, characterized in that: The high temperature is 200-800° C. and the high pressure is 1-8 Gpa.

4. The method for preparing the flaky phosphorus / titanium carbide composite according to claim 2, characterized in that: The high temperature is 300-700° C. and the high pressure is 2-6 Gpa.

5. The method for preparing the flaky phosphorus / titanium carbide composite according to claim 4, characterized in that: The steps are: (1) mixing and grinding red phosphorus and titanium carbide nanosheets uniformly, and then pressing them into blocks; (2) After applying pressure to the block of step (1) to 2-6 GPa, the temperature is raised to 300-700°C, and the temperature and pressure are maintained to react until the reaction is complete. After cooling, a flaky phosphorus / titanium carbide composite is obtained.

6. The method for preparing the flaky phosphorus / titanium carbide composite according to claim 5, characterized in that: The time of the heat preservation and pressure maintenance reaction in the step (2) is 1-60 minutes.

7. A flake phosphorus / titanium carbide composite prepared by the method according to any one of claims 1 to 4.

8. The flaky phosphorus / titanium carbide composite according to claim 7, characterized in that: The flaky phosphorus / titanium carbide composite comprises a heterogeneous junction formed by amorphous red phosphorus and crystalline black phosphorus; the composite further comprises titanium carbide nanosheets, and the red phosphorus-black phosphorus heterogeneous junction is loaded on the surface of the titanium carbide nanosheets to form a phosphorus / titanium carbide composite.

9. A negative electrode material, characterized in that: The negative electrode material is the flaky phosphorus / titanium carbide composite material as claimed in claim 8.

10. A sodium ion battery prepared using the negative electrode material according to claim 9.

Citation Information

Patent Citations

  • Negative electrode active material and preparation and application thereof

    CN111785946A